Philippine MSMEs - Impact on Sustainable Economic Development in Employment Generation, Income Inequality, and Poverty - Eliza Nicole Adviento; Charlene Laine Bumanlag; Shannen Rose Fajarito; Peter Jeff Camaro (Faculty of Science and Technology University of Pramita Indonesia, 2022)
In the Philippines, the MSME sector is considered to be a significant driving force in boosting economic productivity addressing poverty, income inequality, and high unemployment rates. This study aims to answer, “How impactful are the role of MSMEs on employment generation, income inequality, and poverty in the Philippines?”. Most studies show that MSMEs (regressor) positively impact employment generation, income inequality, and poverty alleviation (regressands) however, some studies show that MSME negatively impacts labor productivity which affects employment generation; MSME and poverty alleviation has a negative association, whereas as MSME industries flourish, poverty incidence also increases; and MSME negatively affect income inequality wherein as MSMEs flourish, the income gap between the rich and the poor is also growing. The researchers collected regional secondary data from the Philippine Statistics Authority and published academic journal online, determined using panel least squares regression analysis to evaluate the relationship between the controlled and observed variables. The study proved that there is a negative correlation between MSMEs and employment generation, income inequality, and poverty alleviation, which means that the dependent variables have an impact on the MSMEs.